Efficient removal of heavy metal ions using hydrophilic thiacalix[4]arene doped polyaniline prepared by emulsion polymerization: conductivity, isotherm and kinetic study. (17th April 2015) - Norouzian, Rafieh‐Sadat; Lakouraj, Moslem M.
<x xml:space="preserve">Abstract</x> The adsorption capacity of conductive polyaniline doped by thiacalix[4]arene tetrasulfonate (PANI–TCAS) towards Cu(II), Cd(II), Co(II) and Cr(III) was investigated through batch adsorption techniques, and the extent of adsorption was measured as a function of pH, initial metal ion concentration and contact time. It was found that the metal ion removal reached maximum at pH 8.0 and remained constant after 60 min. Experimental data was fitted to Langmuir, Freundlich, Redlich–Peterson and Temkin equation models with the maximum adsorption capacity calculated to be 833.3, 555.5, 526.3 and 500 for Cr3+, Cu2+, Co2+ and Cd2+, respectively, from the Langmuir isotherm model. The kinetic study was carried out through pseudo‐first‐order, pseudo‐second‐order, Elovich kinetic and intraparticle diffusion models in which the related correlation coefficient for each kinetic model showed that the pseudo‐second‐order rate equation was better described by the adsorption process. XRD spectra, SEM and TEM images of the adsorbent revealed a homogeneous distribution of nano‐sized particle structure with a porous surface, the morphology of which brings about high adsorption capacity for the PANI–TCAS molecular nanocomposite which in turn was observed by the AFM micrograph. The conductivity of thiacalix[4]arene tetrasulfonate doped polyaniline after metal ion adsorption was also assessed, and the four‐probe measurement technique revealed conductivity increment as high as 102.4 S cm−1 with a 100 order of magnitude enhancement. Copyright © 2015 John Wiley & Sons, Ltd.